2017
DOI: 10.1002/cssc.201700779
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Vacancy Engineering of Co3O4 Nanocrystals through Coupling with Metal Support for Water Oxidation

Abstract: Oxygen vacancies can help to capture oxygen-containing species and act as active centers for oxygen evolution reaction (OER). Unfortunately, effective methods for generating a high amount of oxygen vacancies on the surface of various nanocatalysts are rather limited. Here, we described an effective way to generate oxygen-vacancy-rich surface of transition metal oxides, exemplified with Co O , simply by constructing highly coupled interface of ultrafine Co O nanocrystals and metallic Ti. Impressively, the amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(54 citation statements)
references
References 57 publications
3
51
0
Order By: Relevance
“…We initially tested the electrocatalytic performance of the Gr‐based electrode for gas evolution processes, involving the in situ formation of hydrogen or oxygen gas bubbles at the interface of electrolyte and the catalyst. Obviously, stabilizing the catalyst‐liquid interface of the electrode and electrolyte (Figure a, b) without the formation of additional gas layers (Figure c, d) is of key importance to keep the active sites exposed to the electrolyte and thus maintain the current output of the electrode . Owing to the superadsorbance of graphene, it adsorbs both polar and nonpolar molecules in large quantities.…”
Section: Figurementioning
confidence: 90%
“…We initially tested the electrocatalytic performance of the Gr‐based electrode for gas evolution processes, involving the in situ formation of hydrogen or oxygen gas bubbles at the interface of electrolyte and the catalyst. Obviously, stabilizing the catalyst‐liquid interface of the electrode and electrolyte (Figure a, b) without the formation of additional gas layers (Figure c, d) is of key importance to keep the active sites exposed to the electrolyte and thus maintain the current output of the electrode . Owing to the superadsorbance of graphene, it adsorbs both polar and nonpolar molecules in large quantities.…”
Section: Figurementioning
confidence: 90%
“…In catalytic systems, intrinsic structural defects can distinctly enhance the catalytic activity of nanocrystals [7][8][9] . Motivated by the advantages for oxygen vacancies, many researchers have focused on the development of new methods and approaches to generate appropriate density of defects on nanocrystals [10][11][12] . Owing to its low-cost, outstanding redox capability and favorable electrical conductivity, Co 3 O 4 represents a promising candidate in various fields, including water splitting 13 , lithium-ion battery 14 , and particularly the field of heterogeneous catalysis 15,16 .…”
mentioning
confidence: 99%
“…The XPS and Raman analysis demonstrated that NiOOH (Ni 3+ ) was formed during the OER. In addition, the CV of the Ti@Ni 0.85 Se‐THA electrode (Figure S11 in the Supporting Information) proved that the Ni 2+ /Ni 3+ pairs act as an active species for the oxidation of water molecules …”
Section: Resultsmentioning
confidence: 96%